2019
DOI: 10.3389/fmicb.2019.01435
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Infection of Blood–Brain Barrier Cells: Consequences of Severe Disease

Abstract: More than 500 million people worldwide are infected each year by any of the four-dengue virus (DENV) serotypes. The clinical spectrum caused during these infections is wide and some patients may develop neurological alterations during or after the infection, which could be explained by the cryptic neurotropic and neurovirulent features of flaviviruses like DENV. Using in vivo and in vitro models, researchers have demonstrated that DENV can affect the cells from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 273 publications
(189 reference statements)
0
38
0
Order By: Relevance
“…Another possible mechanism of CNS infection by SARS-CoV-2 is through infection of vascular ECs, which have already been reported to be infected by SARS-CoV-2 ( Varga et al., 2020 ). In addition, other neurovirulent viruses, such as some strains of Dengue Fever virus, are also capable of reaching the CNS by infecting ECs to cross the BBB ( Calderon-Pelaez et al., 2019 ). Apart from direct EC infection, the important systemic inflammation observed in COVID-19 patients can also induce BBB disruption ( Sankowski et al., 2015 ), allowing potential entry of infected leukocytes into the CNS.…”
Section: Coronaviruses Sars-cov-2 and The Central Nervous Systemmentioning
confidence: 99%
“…Another possible mechanism of CNS infection by SARS-CoV-2 is through infection of vascular ECs, which have already been reported to be infected by SARS-CoV-2 ( Varga et al., 2020 ). In addition, other neurovirulent viruses, such as some strains of Dengue Fever virus, are also capable of reaching the CNS by infecting ECs to cross the BBB ( Calderon-Pelaez et al., 2019 ). Apart from direct EC infection, the important systemic inflammation observed in COVID-19 patients can also induce BBB disruption ( Sankowski et al., 2015 ), allowing potential entry of infected leukocytes into the CNS.…”
Section: Coronaviruses Sars-cov-2 and The Central Nervous Systemmentioning
confidence: 99%
“…DENV, like ZIKV, is a member of the Flavivirus genus. More than 500 million people worldwide are infected each year by any of the four-DENV serotypes [23]. To further verify the importance of the KRRK basic residues of IFITM1 against viruses, IFITM1 and KRRK mutants were used to detect their restriction on the DENV-2 TSV01 strain in Vero cells.…”
Section: Krrk Basic Residues Of Ifitm1 Are Key For the Restriction Onmentioning
confidence: 99%
“…DENV can be identified in the cerebrospinal fluid and the brain tissue of encephalitis patients ( Verma et al, 2014 ). It has been suggested that DENV can enter neuronal systems through membrane receptors and contribute to neurological manifestations, including encephalitis, encephalopathy, and dengue-associated neuromuscular complications ( Calderon-Pelaez et al, 2019 ). Appropriate medical interventions are needed to prevent neurological complications and death.…”
Section: Introductionmentioning
confidence: 99%